Addict to win? A different approach to doping. Issue 11 (21st October 2010) - D'Angelo, Carlos; Tamburrini, Claudio
Abstract : Traditionally the doping debate has been dominated by those who want to see doping forbidden (the prohibitionist view) and those who want to see it permitted (the ban abolitionist view). In this article, the authors analyse a third position starting from the assertion that doping use is a symptom of the paradigm of highly competitive elite sports, in the same way as addictions reflect current social paradigms in wider society. Based upon a conceptual distinction between occasional use, habitual use and addiction, and focusing on the physical and/or mental dependency caused by the addictive use of a certain drug, we argue that marihuana, stimulants and anabolic steroid abuse—the most frequently detected substances in doping tests—satisfies at least one, often both, of these conditions. A conclusion to be drawn from the authors' arguments is that the prohibitionist view is inappropriate for dealing with doping, as the severe sanctions attached to it will cut the doper off her/his social and professional environment, thereby risking reinforcing her/his addictive conduct. But the ban abolitionist view seems inappropriate as well. At first sight, it seems neither rational nor humane not to intervene when confronted with conduct which is highly harmful for the individual and upon which she has reduced or no control whatsoever. Instead the authors' proposal will be to contextualise dopers' conduct within sport healthcare and see it strictly in relation to each athlete's personal background. Developing preventive programmes—implemented through person-tailored counselling and eventually treatment, rather than severe sanctions or the mere lifting of the ban—seems to be a more reasonable, and probably more efficient, way of conducting 'the war against doping'.